Analisis Respon Pembacaan Sensor Beban (Load Cell) dengan Menggunakan Autonics TK4S - Mubarok, Moh Rizqi; Amiruddin, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
An analysis of the characteristics of the temperature control system has been carried out on a prototype clothing dryer based on the Autonics TK4S-14RN. A control system is a process control system that aims to obtain a variable at a certain value. The closed loop control system is the control system used in this research which consists of control implementation elements in the form of on/off control types on the load system (load cell). The correction element is in the form of the Autonics TK4S-14RN programming procedure as software. The measurement element uses a PT100 RTD sensor series with a sensitivity of 0.3931Ω/℃, an inaccuracy of ±0.000673, a precision and accuracy error percentage of 0.17% and 1.9%. Characterization of the Autonics TK4S-14RN as a load control (load cell) was carried out to review transient and steady-state responses. The test results obtained an insulated system with a deviation of 0.1℃, so that the steady state system was 0.28% of SV, with ts=140-268 s and Mp = 0.85-1.42%. From the results of this research, the control system created can be used as a basis for load control (load cell).